Characterization of phytoconstituents and evaluation of antimicrobial activity of silver-extract nanoparticles synthesized from Momordica charantia fruit extract - Md. Mamun Or Rashid; Kazi Nahid Akhter; Jakir Ahmed Chowdhury; Foysal Hossen; Md. Saddam Hussain; Md. Tanvir Hossain (BMC Complementary and Alternative Medicine, 2017)
Abstract Background Our present study was conducted to characterize the phytoconstituents present in the aqueous extract of Momordica charantia and evaluate the antimicrobial efficacy of silver-extract nanoparticles (Ag-Extract-NPs). Methods Silver nanoparticles (AgNPs) were prepared by reducing AgNO3; and NaBH4 served as reducing agent. After screening of phytochemicals; AgNPs and aqueous extract were mixed thoroughly and then coated by polyaniline. These NPs were characterized by using Visual inspection, UV spectroscopy, FTIR, SEM and TEM techniques. Antimicrobial activities were assessed against Staphylococcus aureus, Salmonella typhi, Escherichia coli and Pseudomonas aeruginosa. Results Aqueous extract of M. charantia fruits contain alkaloid, phenol, saponin etc. UV–Vis spectrum showed strong absorption peak around 408 nm. The presence of –CH, −NH, −COOH etc. stretching in FTIR spectrum of Ag-Extract-NPs endorsed that AgNPs were successfully capped by bio-compounds. SEM and TEM result revealed that synthesized NPs had particle size 78.5–220 nm. Ag-Extract-NPs showed 34.6 ± 0.8 mm zone of inhibition against E. coli compared to 25.6 ± 0.5 mm for ciprofloxacin. Maximum zone of inhibition for Ag-Extract-NPs were 24.8 ± 0.7 mm, 26.4 ± 0.4 mm, 7.4 ± 0.4 mm for S. aureus, P. aeruginosa and S. typhi. We found that Ag-Extract-NPs have much better antibacterial efficacy than AgNPs and M. charantia extract has individually. It is also noticed that gram negative bacteria (except S. typhi) are more susceptible to Ag-Extract-NPs than gram positive bacteria. Conclusion Ag-Extract-NPs showed strong antibacterial activity. In order to make a reliable stand for mankind, further study is needed to consider determining the actual biochemical pathway by which AgNPs-extracts exert their antimicrobial effect.